PENGARUH PERMEABILITAS RESERVOIR TERHADAP PEMBENTUKAN LAPANGAN PANASBUMI: THE EFFECT OF RESERVOIR PERMEABILITY ON ESTABLISHMENT OF GEOTHERMAL FIELDS - Hermina Haluk (JISTECH: Journal of Information Science and Technology, 2014)
Generaly geothermal is a manifestation of earth heat which accumulated since earth formed. In nature the heat generate what is called geothermal system. One of main aspect of a geothermal system is geothermal reservoir. The reservoir functions as water container that will be heated by heat sources or occupied by vapor that already generated deep down the earth. One of the physical property of geothermal reservoir rock is permeability. The permeability is the rock property to allow fluids to flow through the interconnected pores within the rock which will control the productivity of the reservoir. A good permeability allows quantities of water get into the reservoir that will increased the vapor/hot water discharge.